Relations between selected social characteristics and meeting basic human needs - Hadner, Maja (Journal for Geography, 2018)
The composition provides findings on the importance of the place of residence and the selected socioeconomic characteristics in meeting basic human needs and represents the role of the place of residence, age, material situation and lifestyle in the individual's activity in space. Based on the data, obtained through interview (16 people), it was established that age and material situation affect the activity of individuals in space more intensively than the place of residence and the way of living.